Varieties of Belief over Time: Reflections from a Longitudinal Study of Youth and Belief - Day, Abby (Journal of contemporary religion, 2013)
This article reports longitudinal research involving young people in adolescence and early adulthood, focusing on questions about belief and identity. The author finds that significant varieties of belief—propositional, felt (emotional/embodied), performative—were created and sustained through social relationships. A seven-part analytical model permits holistic, organic analysis to identify the shifting and mutually interdependent dimensions of belief: content, source, practice, salience, function, time, and place. The articles forms part of a special issue of the Journal of Contemporary Religion, entitled "Belief as Cultural Performance".